O processo de inclus??o escolar de alunos com Dist??rbio do Processamento Auditivo Central (DPAC) em escolas p??blicas de Bras??lia - Abreu, Micheliny Jafar de Souza (2016)
This work aimed at understanding the process of inclusion in education of students with Central Auditory Processing Disorders (CAPD) based on individual elements and context of the bioecological model as perceived by students, their parents and teachers. We conducted a methodological approach to qualitative research content analysis with semi-structured interviews. Data collection was performed in two educational institutions of public regular education Bras??lia DF. Participated in the survey: Two students with CAPD, her parents, two teachers from each school, a regular room and an educational support room / resource, school guidance counselors and the coordinator of Centro de Atendimento ao Surdo (CAS), totalizing 11 participants. Thus the research sought to understand the local reality to guide the actions and educational practices that can assist in the realization of the inclusive process of students with CAPD. It was found that the continuation of aid offered by the school, the good relationship between teacher-student and maintenance and permanence of a school routine and specialized services contributed to learning and socialization, which caused a positive impact on the development of students. Finally, it was found that there is a need to improve teacher training and teaching practices in the classroom and the school inclusion requires effort and participation of all involved.